2023
DOI: 10.3389/fendo.2023.1098638
|View full text |Cite
|
Sign up to set email alerts
|

Risk of diabetic retinopathy and retinal neurodegeneration in individuals with type 2 diabetes: Beichen Eye Study

Abstract: ObjectiveOur aim was to evaluate associations of different risk factors with odds of diabetic retinopathy (DR) diagnosis and retinal neurodegeneration represented by macular ganglion cell-inner plexiform layer (mGCIPL).MethodsThis cross-sectional study analyzed data from individuals aged over 50 years examined between June 2020 and February 2022 in the community-based Beichen Eye Study on ocular diseases. Baseline characteristics included demographic data, cardiometabolic risk factors, laboratory findings, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Although it is generally accepted that hypertension is associated with the risk of DR, there are conflicting views on this relationship in previous studies. Numerous studies have confirmed that hypertension can be a potential risk factor for DR. A cross-sectional study by Yang et al revealed that the progression of diabetes, hypertension, and HbA1c are independent risk factors for DR formation in patients with diabetes but do not impact the diagnostic rate of DR in the general population (22). Some RCTs have proved that good regular blood pressure control is advantageous for the emergence of DR. Higher blood pressure level may be associated with the occurrence and progress of DR; however, mildly elevated hypertension does not significantly impact the development of DR (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is generally accepted that hypertension is associated with the risk of DR, there are conflicting views on this relationship in previous studies. Numerous studies have confirmed that hypertension can be a potential risk factor for DR. A cross-sectional study by Yang et al revealed that the progression of diabetes, hypertension, and HbA1c are independent risk factors for DR formation in patients with diabetes but do not impact the diagnostic rate of DR in the general population (22). Some RCTs have proved that good regular blood pressure control is advantageous for the emergence of DR. Higher blood pressure level may be associated with the occurrence and progress of DR; however, mildly elevated hypertension does not significantly impact the development of DR (23).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with T2D have an increased risk of developing various complications such as cardiovascular disease, neuropathy and retinopathy, which can significantly affect their quality of life [ 9 ]. However, effective management of T2D requires an understanding of the socio-behavioral determinants that influence health-related quality of life [ 10 ].…”
Section: Introductionmentioning
confidence: 99%